2023
DOI: 10.2147/cia.s425393
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Predictive Value of Inflammatory Biomarkers for the Risk of Stroke-Associated Pneumonia in Patients with Acute Ischemic Stroke

Jingyi Li,
Haowen Luo,
Yongsen Chen
et al.

Abstract: To investigate the predictive value of various inflammatory biomarkers in patients with acute ischemic stroke (AIS) and evaluate the relationship between stroke-associated pneumonia (SAP) and the best predictive index. Patients and Methods: We calculated the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), monocyte-tolymphocyte ratio (MLR), prognostic nutritional index (PNI), systemic inflammation response index (SIRI), systemic immune inflammation index (SII), Glasgow prognostic score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Firstly, our recent study indicated that hospitalized patients with high SIRI had an increased risk of DVT, which is a relatively common cause of death worldwide ( 40 ). Meanwhile, high SIRI level was also found to be an independent risk factor for pneumonia ( 41 , 42 ), which was proved to be the most significant mediator contributing to the largest proportions of excess mortality following hip fracture ( 43 ). In addition, Lu et al reported that SIRI was positively correlated with the occurrence of postoperative delirium in older patients with hip arthroplasty surgery ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, our recent study indicated that hospitalized patients with high SIRI had an increased risk of DVT, which is a relatively common cause of death worldwide ( 40 ). Meanwhile, high SIRI level was also found to be an independent risk factor for pneumonia ( 41 , 42 ), which was proved to be the most significant mediator contributing to the largest proportions of excess mortality following hip fracture ( 43 ). In addition, Lu et al reported that SIRI was positively correlated with the occurrence of postoperative delirium in older patients with hip arthroplasty surgery ( 44 ).…”
Section: Discussionmentioning
confidence: 99%